1999
DOI: 10.1001/archinte.159.18.2151
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Dietary Magnesium and the Risk for Type 2 Diabetes Mellitus

Abstract: Among white participants, low serum magnesium level is a strong, independent predictor of incident type 2 diabetes. That low dietary magnesium intake does not confer risk for type 2 diabetes implies that compartmentalization and renal handling of magnesium may be important in the relationship between low serum magnesium levels and the risk for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
281
3
9

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(311 citation statements)
references
References 49 publications
18
281
3
9
Order By: Relevance
“…[18][19][20][21][22][23] Recently, we reported that appropriate supplementation of Mg 2ϩ suppressed the decrease of Mg 2ϩ concentration and the increase of Ca 2ϩ concentration in SCR rat lenses, resulting in delayed cataract development. 24) These findings suggest that the Mg 2ϩ concentration in the lens relates to the progression of lens opacification.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Recently, we reported that appropriate supplementation of Mg 2ϩ suppressed the decrease of Mg 2ϩ concentration and the increase of Ca 2ϩ concentration in SCR rat lenses, resulting in delayed cataract development. 24) These findings suggest that the Mg 2ϩ concentration in the lens relates to the progression of lens opacification.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of magnesium is raised in people with diabetes and it has been suggested that hypomagnesaemia is a possible consequence of diabetes (Khan et al, 1999). However, prospective studies have found both low serum magnesium and low dietary magnesium intakes to be inversely associated with the incidence of T2DM, suggesting that low magnesium intake and status predates the diabetic condition (Colditz et al, 1992;Salmeron et al, 1997a, b;Kao et al, 1999;Meyer et al, 2000). Further, Liu et al (2000) found that the median dietary magnesium intakes of female nurses increased from 248 to 342 mg/day across quintiles of whole grain intake.…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…22 These findings suggest that hypomagnesemia could be involved in the pathogenesis of cardiovascular disease, 22 insulin resistance, 25 -27 and type 2 diabetes. 28 Although the experimental magnesium deficiency in rats induces an exacerbated immune stress response 29 that increase the levels of acute-phase reactants, the significance of this finding has received little attention.…”
Section: Introductionmentioning
confidence: 99%